Conversational Differentiated Instruction: Tutor's Strategies in Fostering Learners' Participation in Non-Formal Daily Talk Sessions - Nadila Lesti Ayu Difani; Putu Dian Danayanti Degeng (Universitas Negeri Medan, 2026)
This exploratory single-case study investigates the pedagogical strategies employed by a single tutor to foster learners’ participation during Daily Talk sessions at English Cafe Malang, a unique non-formal, cafe-based learning environment. Employing a qualitative design, data were collected through semi-structured interview insights coupled with direct observations of learner dynamics to ensure data triangulation. The results indicate that the tutor relies on group sharing within a conversational circle, utilizing relatable topics and a mandatory pre-speaking vocabulary module. To accommodate the highly heterogeneous language proficiency levels, the tutor implements spontaneous, “on-the-fly” conversational Differentiated Instruction (DI) alongside immediate, low-pressure translation support. Triangulated observation data reveal that these strategies successfully trigger strong emotional stability and independent cognitive strategies among participants. However, the relaxing environment presents a pedagogical trade-off, leading to behavioral distractions such as smartphone use and side-talk. While the scope of this study is limited to a single unit of analysis, it offers valuable micro-level insights into non-formal language instruction.